2001
DOI: 10.1002/1521-3773(20010716)40:14<2660::aid-anie2660>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Dicyclopenta[a,d]cyclooctene: A [14]Annulene Containing Two Zero-Atom Cross-Links

Abstract: 14π‐Electrocyclization across the two pentafulvenoid moieties of pentafulvene 1 occurs upon heating to provide dicyclopenta[a,d]cyclooctene 2 [Eq. (1)]. The nonalternant hydrocarbon 2 shows diatropic character and a distinctive absorption spectrum with the longest wavelength maximum at 767 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
(9 reference statements)
2
16
0
Order By: Relevance
“…It exhibits the longest wavelength absorption maxima (λ = 1375 (0.9) nm (eV)). 37 The calculated optical gap at highest D–A strength (|ϵ| = 5 eV) was found to be 0.7 eV, which is very close to the experimentally found absorption (0.9 eV) reported for the 2,7-di(tert-butyl) derivative of the DCPCO isomer. The TDDFT result of the optical absorption (1.0 eV) of DCPCO ( d ) is also in good agreement with experiments.…”
Section: Results and Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It exhibits the longest wavelength absorption maxima (λ = 1375 (0.9) nm (eV)). 37 The calculated optical gap at highest D–A strength (|ϵ| = 5 eV) was found to be 0.7 eV, which is very close to the experimentally found absorption (0.9 eV) reported for the 2,7-di(tert-butyl) derivative of the DCPCO isomer. The TDDFT result of the optical absorption (1.0 eV) of DCPCO ( d ) is also in good agreement with experiments.…”
Section: Results and Discussionsupporting
confidence: 82%
“…The 2,7-di­(terbutyl) derivative of the DCPCO ( d ) isomer is shown in Figure . It exhibits the longest wavelength absorption maxima (λ = 1375 (0.9) nm (eV)) . The calculated optical gap at highest D–A strength (|ϵ| = 5 eV) was found to be 0.7 eV, which is very close to the experimentally found absorption (0.9 eV) reported for the 2,7-di­(tert-butyl) derivative of the DCPCO isomer.…”
Section: Results and Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…[14]Annulene ( 48 , Figure ) was first synthesized in 1960 by Sondheimer and Gaoni . Computational and experimental studies performed since have consistently concluded that the molecule adopts a nonplanar conformation with a delocalized π-bond structure in the solid crystalline state . The nonplanarity is ascribed primarily to nonbonding interactions between the internal protons.…”
Section: 4 [14]annulene241 Aromaticity Probesmentioning
confidence: 99%
“…118 Dicyclopenta[a,d]cyclooctene 88 was synthesized to investigate its aromatic nature as a [14]annulene containing two zero-atom cross-links. 119 Using Pdcatalysed coupling and/or an oxidative coupling reaction, di(6-azulenyl)acetylenes 89 (n = 1 and 2) were prepared. 120 The tripodal polyyne 90 was prepared by the reaction of 1,3,5-triethynylbenzene with 6-tert-butyl-1-iodo-3-(trimethylsilylethynyl)azulene.…”
Section: Nonbenzenoid Aromaticsmentioning
confidence: 99%